Time-Controlled Adaptive Ventilation Does Not Induce Hemodynamic Impairment in a Swine ARDS Model - Lescroart, Mickael; Pequignot, Benjamin; Bitker, Laurent; Pina, Héloïse; Tran, N'Guyen; Hébert, Jean-Louis; Richard, Jean-Christophe; Lévy, Bruno; Koszutski, Matthieu (Frontiers in Medicine, 2022)
BACKGROUND: The current standard of care during severe ARDS is based on low tidal volume (VT) ventilation, at 6 mL/kg of predicted body weight. The time-controlled adaptive ventilation (TCAV) is an alternative strategy, based on specific settings of the airway pressure release ventilation (APRV) mode. Briefly, TCAV reduces lung injury, including: 1) an improvement in alveolar recruitment and homogeneity; 2) reduction in alveolar and alveolar duct micro-strain and stress-risers. TCAV can result in higher intra-thoracic pressures and thus impair hemodynamics resulting from heart-lung interactions. The objective of our study was to compare hemodynamics between TCAV and conventional protective ventilation in a porcine ARDS model. METHODS: In ten pigs (63-73 kg), lung injury was induced by repeated bronchial saline lavages followed by 2 hours of injurious ventilation. The animals were then randomized into two groups: 1) Conventional protective ventilation with a VT of 6 mL/kg and PEEP adjusted to a plateau pressure set between 28 and 30 cmH2O; 2) TCAV group with P-high set between 27 and 29 cmH2O, P-low at 0 cmH2O, T-low adjusted to terminate at 75% of the expiratory flow peak, and T-high at 3 to 4 seconds, with I:E > 6:1. RESULTS: Both lung elastance and PaO2:FiO2 were consistent with severe ARDS after two hours of injurious mechanical ventilation. There was no significant difference in systemic arterial blood pressure, pulmonary blood pressure or cardiac output between Conventional protective ventilation and TCAV. Levels of total PEEP were significantly higher in the TCAV group (p<0.05). Driving pressure and lung elastance were significantly lower in the TCAV group (p<0.05). CONCLUSION: No hemodynamic adverse events were observed in the TCAV group compared as to the standard protective ventilation group in this swine ARDS model, and TCAV appeared to be beneficial to the respiratory system.